2016
DOI: 10.1021/acsami.5b08596
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Spontaneous Pumpless Transportation of Nonpolar Organic Liquids on Extreme Wettability Patterns

Abstract: Spontaneous pumpless transportation (SPT) of liquids has generated tremendous demands in microfluidic systems and advanced devices. However, the transportation of nonpolar organic liquids on open platforms underwater remains a challenge because most existing SPT systems are only designed for use in air. Here, we report a surface-tension-driven SPT system to transport various nonpolar organic liquids using underwater extreme wettability patterns. The patterns were fabricated with a wedge-shaped superoleophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…Prior work has demonstrated water transport/management on wettability‐patterned surfaces where manipulation of liquid movement is achieved in a passive (i.e., no external power input) manner by harnessing surface‐tension forces . Other studies have shown wettability‐engineered systems can be also used for transporting organic liquid droplets on straight, peristome‐mimetic, and underwater wedge‐shaped tracks . In the present work, select regions of the superoleophobic, FS:FD:PMC coating are removed via laser ablation (thus made superoleophilic).…”
Section: Introductionmentioning
confidence: 92%
“…Prior work has demonstrated water transport/management on wettability‐patterned surfaces where manipulation of liquid movement is achieved in a passive (i.e., no external power input) manner by harnessing surface‐tension forces . Other studies have shown wettability‐engineered systems can be also used for transporting organic liquid droplets on straight, peristome‐mimetic, and underwater wedge‐shaped tracks . In the present work, select regions of the superoleophobic, FS:FD:PMC coating are removed via laser ablation (thus made superoleophilic).…”
Section: Introductionmentioning
confidence: 92%
“…By contrast, for wedge shaped SHL-SHB pattern 1 (SSP1) with spacing distance of d1 (4 mm), nucleated droplet constantly grew and merged at SHB regions which were transported into SHL domains after contacting the border of SHL pattern. Driven by inner Laplace pressure gradient [33][34][35][36], pumpless transportation of the condensing water took place at the SHL wedge shaped track pattern (Movie S9 of Supplementary Material). As shown in Figure 8e, neighbouring droplets at the tail end of tracks merged into a large droplet due to close spacing distance of 4 mm, demonstrating fast transition to film-like condensation.…”
Section: Fabrication Of Extreme Wetting Patterns On An Al Platementioning
confidence: 99%
“…4 (a)]. The water droplet impacted on a wedge surface, and then moved from the narrow zone to the wide zone driven by Laplace pressure 27,28,[36][37][38] . Fig.…”
Section: Directional Transport Of Droplets On Water Harvesting Platformmentioning
confidence: 99%